2013
DOI: 10.1016/j.jacc.2013.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulation and Antiplatelets in Atrial Fibrillation Patients After Myocardial Infarction and Coronary Intervention

Abstract: In real-life AF patients with indication for multiple antithrombotic drugs after MI/PCI, OAC and clopidogrel was equal or better on both benefit and safety outcomes compared to triple therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
191
3
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(226 citation statements)
references
References 31 publications
18
191
3
14
Order By: Relevance
“…The study showed that dual antithrombotic therapy significantly reduced the risk of bleeding and was also associated with a lower risk of death or thrombotic events than was triple antithrombotic therapy 19. Data from registries support the WOEST findings 19, 20. More recently, the findings from the open‐label ISAR‐TRIPLE trial,21 which involved 614 patients with an indication for OAC who were undergoing drug‐eluting stent (DES) implantation, support a limited duration (6 weeks vs 6 months) of triple antithrombotic therapy 22…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The study showed that dual antithrombotic therapy significantly reduced the risk of bleeding and was also associated with a lower risk of death or thrombotic events than was triple antithrombotic therapy 19. Data from registries support the WOEST findings 19, 20. More recently, the findings from the open‐label ISAR‐TRIPLE trial,21 which involved 614 patients with an indication for OAC who were undergoing drug‐eluting stent (DES) implantation, support a limited duration (6 weeks vs 6 months) of triple antithrombotic therapy 22…”
Section: Introductionmentioning
confidence: 65%
“…As noted above, antiplatelet monotherapy is not sufficient for stroke prevention, nor is dual antiplatelet therapy alone (although this has not been tested with the more potent drugs). On the other end of the spectrum, use of triple antithrombotic therapy for 1 year has an unacceptable increased risk of bleeding 13, 20, 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 625 initial citations, 16 eligible studies including a total of 9185 patients were identified in the present meta‐analysis,4, 5, 6, 7, 12, 14, 15, 19, 20, 21, 22, 23, 24, 25, 26, 27 with 5680 patients in the triple therapy group and 3505 in the dual therapy group (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies were identified in the DAPT subgroup,4, 5, 6, 7, 19, 20, 21, 22, 23, 24, 25, 26 with the other 4 studies included in the OAC/C subgroup 12, 14, 15, 27…”
Section: Resultsmentioning
confidence: 99%